Pengaruh Kualitas Pelayanan, Harga dan Lokasi Terhadap Kepuasan Pelanggan Bengkel UD. Jaya Utama Motor Mojokerto - Putri, Anis; Wahyudi, Wahyudi; Nuraeni, Eny (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2025)
The purpose of this study was to determine the effect of service quality, price, and location on customer satisfaction at UD. Jaya Utama Motor Mojokerto partially, simultaneously or dominantly. The research method used is a quantitative method. The population in this study were UD workshop customers. Jaya Utama Motor Mojokerto. The sample in this study amounted to 80 respondents. The data analysis method used is multiple linear regression, the coefficient of determination and hypothesis testing using the SPSS version 26 program. Based on the results of the study, it is shown that the results of the multiple linear regression coefficients are Y = 2.126 + 0.461 X1 + 0.236 X2 + 0.771 X3. The service quality variable partially influences customer satisfaction. The price variable partially affects customer satisfaction. Location variables partially affect customer satisfaction. Variables of service quality, price and location simultaneously affect customer satisfaction. Location variable has the most dominant influence on customer satisfaction.